Postoperative permanent section evaluation of Mohs micrographic surgery debulk specimens does not result in upstaging of cutaneous squamous cell carcinoma compared to stage at the completion of surgery: A retrospective case seriesCapsule Summary - Andrea Gilmore, MD; Brianna Castillo, MD; Nicholas Golda, MD; Kara Braudis, MD; Emily Smith, MD (Elsevier, 2024)
Background: Mohs micrographic surgery (MMS) is used for the treatment of high-risk cutaneous squamous cell carcinoma (cSCC). MMS examines the surgical margins in real time and does not commonly examine the central component of the tumor. Objective: To determine if debulk specimens provide additional details relevant to tumor staging not gained from routine MMS. Methods: A retrospective chart review of debulk specimens taken during MMS for cSCC was performed. Dermatopathology reports were analyzed and tumors were staged using Brigham and Women's Hospital and American Joint Committee on Cancer's 8th edition staging systems. Results: Permanent section evaluation of debulk specimens did not result in clinically meaningful information for staging that could not be gained from MMS layers or initial biopsy analysis. Limitations: A single institution, and a small sample size of 39 tumors. Conclusions: Evaluation of debulk specimens during MMS may not always be an effective use of time or health care resources.